Association Between Prompt Defibrillation and Epinephrine Treatment With Long-Term Survival After In-Hospital Cardiac Arrest. Issue 19 (8th May 2018) - Patel, Krishna K.; Spertus, John A.; Khariton, Yevgeniy; Tang, Yuanyuan; Curtis, Lesley H.; Chan, Paul S.; Chan, Paul S.; Grossestreuer, Anne; Moskowitz, Ari; Edelson, Dana P.; Ornato, Joseph P.; Peberdy, Mary Ann; et al.
Abstract : Background: Prior studies have reported higher in-hospital survival with prompt defibrillation and epinephrine treatment in patients with in-hospital cardiac arrest (IHCA). Whether this survival benefit persists after discharge is unknown. Methods: We linked data from a national IHCA registry with Medicare files and identified 36 961 patients ≥65 years of age with an IHCA at 517 hospitals between 2000 and 2011. Patients with IHCA caused by pulseless ventricular tachycardia or ventricular fibrillation were stratified by prompt (⩽2 minutes) versus delayed (>2 minutes) defibrillation, whereas patients with IHCA caused by asystole or pulseless electric activity were stratified by prompt (⩽5 minutes) versus delayed (>5 minutes) epinephrine treatment. The association between prompt treatment and long-term survival for each rhythm type was assessed with multivariable hierarchical modified Poisson regression models. Results: Of 8119 patients with an IHCA caused by ventricular tachycardia or ventricular fibrillation, the rate of 1-year survival was higher in those treated with prompt defibrillation than with delayed defibrillation (25.7% [1466 of 5714] versus 15.5% [373 of 2405]; adjusted relative risk [RR], 1.49; 95% confidence interval [CI] 1.32–1.69; P <0.0001). This survival advantage persisted at 3 years (19.1% versus 11.0%; adjusted RR, 1.45; 95% CI, 1.23–1.69; P <0.0001) and at 5 years (14.7% versus 7.9%; adjusted RR, 1.50; 95% CI, 1.22–1.83; P <0.0001). Of 28 842 patients with an IHCA caused by asystole/pulseless electric activity, the rate of 1-year survival with prompt epinephrine treatment was higher than with delayed treatment (5.4% [1341 of 24 885] versus 4.3% [168 of 3957]; adjusted RR, 1.20; 95% CI, 1.02–1.41; P =0.02), but this survival benefit was no longer present at 3 years (3.5% versus 2.9%; adjusted RR, 1.17; 95% CI, 0.95–1.45; P =0.15) and at 5 years (2.3% versus 1.9%; adjusted RR, 1.18; 95% CI, 0.88–1.58; P =0.27). Conclusions: Prompt defibrillation for IHCA caused by ventricular tachycardia or ventricular fibrillation was associated with higher rates of long-term survival throughout 5 years of follow-up, whereas prompt epinephrine treatment for asystole/pulseless electric activity was associated with greater survival at 1 year but not at 3 or 5 years. By quantifying the greater survival associated with timely defibrillation and epinephrine administration, these findings provide important insights into the durability of survival benefits for 2 process-of-care measures in current resuscitation guidelines. Abstract : Supplemental Digital Content is available in the text.